2008
DOI: 10.1002/bio.1016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a two‐hour judo training session on the neutrophil immune functions in university judoists

Abstract: The present study examined the effects of judo training on neutrophil and related functions. We measured and studied changes in the neutrophil and its related functions in 22 male university judoists immediately before (Pre values) and immediately after (Post values) a 2 h training session: reactive oxygen species (ROS) production capability, phagocytic activities (PA) and serum opsonic activity (SOA). Neutrophil count in whole blood, myogenic enzymes (creatine kinase, lactate dehydrogenase, aspartate aminotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
4
21
2
6
Order By: Relevance
“…We measured the effect of CWI on AST and ALT enzymes in combat-sport athletes. Despite the increases that we observed and that Umeda et al 44 observed after a typical judo training session, Yamamoto et al 45 measured lower serum levels of AST, LDH, and CK posttraining in judokas engaged in a long-term training period (6 months), suggesting that one important adaptation of long-term training is less or no muscle damage. Whereas few investigators have measured the AST and ALT enzymes, Yamamoto et al 45 reported increased values in judo athletes at immediate posttraining but not at 24 hours postrecovery.…”
Section: Discussioncontrasting
confidence: 88%
“…We measured the effect of CWI on AST and ALT enzymes in combat-sport athletes. Despite the increases that we observed and that Umeda et al 44 observed after a typical judo training session, Yamamoto et al 45 measured lower serum levels of AST, LDH, and CK posttraining in judokas engaged in a long-term training period (6 months), suggesting that one important adaptation of long-term training is less or no muscle damage. Whereas few investigators have measured the AST and ALT enzymes, Yamamoto et al 45 reported increased values in judo athletes at immediate posttraining but not at 24 hours postrecovery.…”
Section: Discussioncontrasting
confidence: 88%
“…However, it must also be considered that the training loads and sports level of athletes in this study were not similar, and it could explain this higher CK response. Also, the physiological shift of CK activity post-exercise in our study is according with that observed by Umeda et al [33], who demonstrated a physiological increase in CK (293.9 ±112.3 U.L -1 ) after standard judo training consisting of a warm-up, 70-min of randori and a cool-down. The structure and the total duration of our training session (65 minutes approximately, excluding the 15 minutes of warm-up and 5 minutes of a cool-down) was very similar to this study, and the physiological increase of CK level in both studies could be considered similar, although that the evident differences between both martial arts would limit these comparisons.…”
Section: Blood Creatine Kinase Concentrationsupporting
confidence: 92%
“…[6] In this paper, we measured serum enzymes related to physical load. [4,16] No significant difference between subjects and within experimental days was observed in the enzyme levels ( Table 2). These results suggest that the summer camp is well planned and managed by experienced staff.…”
Section: Discussionmentioning
confidence: 60%
“…We previously reported a CL measurement technique using a parallel luminometer with a cooled charge-coupled device (CCD) camera, and the parallel luminometer can measure 96 samples simultaneously with excellent reproducibility. [11] Some studies concerning the relations of SOA with specific immune reactions have been reported in this journal [12][13][14][15][16] No significant correlation between levels of SOA and immunoglobulin after acute exercise [13] and during a 21 day metabolic study [14] were reported, but significant correlations between depressed SOA levels and decreased immunoglobulin levels were observed during 20 days of training. [12] In this study, to evaluate the effects of the summer training camp on non-specific humoral immunity, we used the CL technique to measure ROS generation from pooled human neutrophils as an indicator of SOA.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation